(3LhGgQ GdcdGe TQM TQGFY GdESdGes - (3GdfLaj, eMeO GdfLaj, eMeO MSf Hf HGbQ, J (B1266(3g` (B1850(3es ((3YHO Gddg Hf edG eMeO Jbjs)
(3ChdgG (B:s
(3ChdgG(B: (3hGdaJhi TGed dcd ef GdeGdcjf hef aj McegeG hGdhcjdjf hGdeNJdajf Hd aj GdQjGV KHhJg ddeHGjYjf ShGA cGf GdYbO dgeG Ch dZjQgeGs
(3BNQgG (B:s
(3BNQgG(B: (3HGdfSHI Edi NUhU GdLGQjI jJYOi Edi ZjQgG ef GdCUhd GdUGeJI hGdfGWbI hNUhU CQV GdUdM adG jdMb Sge ZjQge ef eMJQej GdeGd Hd dG jHYO GdGbJUGQ Ydi chf GdeTJQj QLdGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf, L (B3: 214s
(3GdPQjYI, L (B5: 196s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis